Pistes de renouveau syndical : défis et enjeux : Introduction / Paths to Union Renewal: Challenges and Issues: Introduction - Haiven, Larry; Lévesque, Christian; Roby, Nicolas (Relations industrielles / Industrial Relations, 2006)
Editorial introduction to the theme of the issue. Includes bibliography.

Régulation du travail et de l’emploi à l’ère numérique : Introduction - Lévesque, Christian; Fairbrother, Peter; Roby, Nicolas (Relations industrielles / Industrial Relations, 2020)
Ce numéro thématique cherche à comprendre comment le numérique est venu perturber et réorganiser la régulation du travail et de l’emploi et comment il peut conduire à des formes d’expérimentation organisationnelle et institutionnelle.

Digitalization and Regulation of Work and Employment: Introduction - Lévesque, Christian; Fairbrother, Peter; Roby, Nicolas (Relations industrielles / Industrial Relations, 2020)
This thematic issue is an effort to understand how digitalization is disrupting and reordering the regulation of work and employment. It also examines how these concerns may lead to organizational and institutional experimentation.